Coalitions in climate mitigation policy re-design processes: The case of the regional greenhouse gas initiative. Issue 127 (January 2022) - Dorman, Maxwell T.; Strong, Aaron L.; Ulibarri, Nicola
Abstract: Using the recently proposed concept of "design coalitions, " this paper analyzes stakeholder participation in a subnational U.S. climate change mitigation policy redesign process. We demonstrate the utility of design coalitions for analyzing policy design processes, contending that it provides an opportunity to examine the understudied "secondary beliefs" of actors as described by the advocacy coalition framework. Our case study consists of an iterative, inductive content analysis of written input to the Regional Greenhouse Gas Initiative's 2016 policy redesign process. We developed a typology of 12 distinct stakeholder types who coalesced in 19 separate design coalitions, each espousing a stance on one of 11 elements of the policy design. These coalitions were dynamic, with radically different sets of stakeholder types participating simultaneously in many different design coalitions without coordination, usually for their own unique reasons. We observe that, although the updated policy reflected many stakeholder's stances, their influence was limited by their exclusion from the agenda-setting phase of this policy redesign process. In this critical era of climate mitigation policy proliferation, it is important to develop a better understanding of climate policy design coalitions and how they engage in and influence climate mitigation policy design processes. Highlights: This research expands knowledge of actor engagement in climate policy design processes. We develop the concept of design coalitions & explore its relevance to climate policy. Here, actors aligned in design coalitions based on the "secondary beliefs" of the ACF. Each type of stakeholder participated in a unique set of design coalitions.